Candidate Species for Florida Aquaculture: Atlantic Croaker, Micropogonias undulatus - R. LeRoy Creswell; Cortney L. Ohs; Christian L. Miller (EDIS)
FA 148, a 5-page illustrated fact sheet by R. LeRoy Creswell, Cortney L. Ohs, and Christian L. Miller, describes this medium-sized fish of the drum family, its culture methods, and summarizes its potential for aquaculture in Florida. Includes references. Published by the UF Department of Fisheries and Aquatic Sciences, May 2007.